Fitur Instagram Shopping Avoskin Dalam Keputusan Pembelian Konsumen Remaja Putri di Kota Surabaya - Febrianti, Andisa Rizky; Arviani, Heidy; Alamiyah, Syifa Syarifah (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The presence of the Instagram Shopping feature has made many businesses and brands take advantage of this feature, including Avoskin, to make it easier for consumers to shop. For this reason, this research was conducted to explore the role of Avoskin's Instagram Shopping feature in the purchasing decisions of young female consumers in the city of Surabaya. The research method was carried out qualitatively, involving 10 high school students as research participants. Data was collected through in-depth interviews and content analysis on Avoskin's Instagram account. The results of the study show that Avoskin's Instagram Shopping feature plays a role in purchasing decisions because it provides an informative display, is easily accessible and minimally distracted, so that consumers can easily find out product and price information. In addition, this feature also makes it easier for consumers to make purchases directly through the Instagram application, which provides a convenient and efficient experience.